Transoral robotic surgery (TORS) with the Medrobotics Flex™ System: first surgical application on humans - Remacle, M.; M. N. Prasad, V.; Lawson, G.; Plisson, L.; Bachy, V.; Van der Vorst, S. (European archives of oto-rhino-laryngology, 2015)
Head and neck surgery can be fraught with difficulties in accessing the pharynx and larynx. Minimally invasive surgery has developed with the recent advances in technology. Currently, we have a variety of high-definition multichannel videoendoscopes and robots in our armamentarium. We present our experience in a new robotic surgical system—’The Medrobotics Flex™ System’ at our tertiary referral unit. We aimed to assess the safety, functionality and ease of use of this new device in this prospective study. Thus far, this is the first study in live human subjects who have undergone surgery for the following conditions: (1) obstructive sleep apnoea involving the base of tongue, the tonsil and the velum; (2) vocal fold polyp; (3) carcinoma of the lateral edge of the tongue. There were no complications in our series and the system provided good visualisation and access to these subsites without compromising safety or success. In summary, we found the Medrobotics Flex™ System to have certain other advantages including ease of set up and use besides being reliable and safe.